Preliminary insights regarding the quality of Kallmet wine, obtained by sequential inoculation with Metschnikowia pulcherrima and Saccharomyces cerevisiae - Mamica Ruci; Renata Kongoli; Francesca Coppola; Mariantonietta Succi; Bruno Testa; Onejda Kyçyk; Julian Karaulli; Fatbardha Lamçe; Massimo Iorizzo (Frontiers in Microbiology)
Non-Saccharomyces wine yeasts have a promising role in biotechnological approaches to enhance wine complexity, particularly by influencing the aromatic profile. Metschnikowia pulcherrima is a non-Saccharomyces yeast that is notable for its antimicrobial activity and diverse enzymatic activities. These properties make this yeast a valid candidate for application as a starter culture in winemaking. This study evaluated the application of M. pulcherrima 62 in sequential inoculation with S. cerevisiae for the production of Kallmet wine, delivered from the indigenous Kallmet grape variety traditionally cultivated in various regions of Albania. The use of different inoculation strategies resulted in significant differences in wine composition, affecting key oenological parameters, the aromatic profile and sensory attributes. M. pulcherrima 62 did not negatively interfere with the fermentation kinetics of S. cerevisiae during fermentation and contributed to wines with lower amounts of ethanol and richer in glycerol, total polyphenols and anthocyanins. Moreover, increased levels of isobutanol, phenylethyl alcohol, isoamyl alcohol and monoterpenes (linalool, geraniol, and nerol) were observed in wines produced with M. pulcherrima 62 and S. cerevisiae in sequential inoculation, compared to wines fermented solely with S. cerevisiae. Finally, sensory analysis revealed a distinct differentiation in the wines, attributable to the modulation of aromatic compounds by M. pulcherrima 62.